Analisis Aktivitas Antioksidan Nanoemulsi Berbaris Tanaman dalam Aplikasi Farmasi dan Kosmetik : Kajian Literatur - Nur Aisyah; Sriwidodo Sriwidodo; Patihul Husni; Santi Sinala (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Plant-based nanoemulsions are increasingly attracting attention in pharmaceutical and cosmetic applications due to their ability to enhance the stability, solubility, and bioavailability of natural active compounds, such as flavonoids, terpenoids, and polyphenols, which possess antioxidant activity. However, the challenge lies in optimizing the nanoemulsion formulation to enhance the efficacy of these compounds. This study aims to explore the potential of plant-based nanoemulsions in enhancing the effectiveness of antioxidant compounds and to provide recommendations for developing more stable and efficient nanoemulsion formulations for pharmaceutical and cosmetic applications. A literature review was conducted by analyzing relevant scientific articles on the use of plant-based nanoemulsions in enhancing antioxidant activity. This study includes various studies that describe the methods of preparation, physicochemical characteristics, and applications of nanoemulsions in the biomedical and cosmetic fields. Plant-based nanoemulsions, such as those using Cordyceps mushroom extract and Mucuna seeds, exhibit stronger antioxidant activity and good stability. Formulations with small particle sizes and uniform particle distribution exhibit higher bioavailability and efficacy, making them promising for application in medical therapy and skin care. Plant-based nanoemulsions offer significant potential for enhancing the efficacy of antioxidant compounds in the pharmaceutical and cosmetic fields. Further development is needed through laboratory and clinical testing to ensure the efficacy and stability of nanoemulsion formulations in real-world applications. Keywords: nanoemulsion, medicinal plants, bioavailability, drug delivery system